A Polyethylenimine-Containing and Transferrin-Conjugated Lipid Nanoparticle System for Antisense Oligonucleotide Delivery to AML. (26th January 2016) - Yuan, Yiming; Zhang, Lijing; Cao, Hua; Yang, Yi; Zheng, Yu; Yang, Xiao-juan
Abstract : Limited success of antisense oligonucleotides (ASO) in clinical anticancer therapy calls for more effective delivery carriers. The goal of this study was to develop a nanoparticle system for delivery of ASO G3139, which targets mRNA of antiapoptotic protein Bcl-2, to acute myeloid leukemia (AML) cells. The synthesized nanoparticle Tf-LPN-G3139 contained a small molecular weight polyethylenimine and two cationic lipids as condensing agents, with transferrin on its surface for selective binding and enhanced cellular uptake. The optimized nitrogen to phosphate (N/P) ratio was 4 to achieve small particle size and high G3139 entrapment efficiency. The Tf-LPN-G3139 exhibited excellent colloidal stability during storage for at least 12 weeks and remained intact for 4 hours in nuclease-containing serum. The cellular uptake results showed extensive internalization of fluorescence-labelled G3139 in MV4-11 cells through Tf-LPN. Following transfection, Tf-LPN-G3139 at 1  µ M ASO level induced 54% Bcl-2 downregulation and >20-fold apoptosis compared to no treatment. When evaluated in mice bearing human xenograft AML tumors, Tf-LPN-G3139 suppressed tumor growth by ~60% at the end of treatment period, accompanied by remarkable pharmacological effect of Bcl-2 inhibition in tumor. In conclusion, Tf-LPN-G3139 is a promising nanoparticle system for ASO G3139 delivery to AML and warrants further investigations.